Accuracy Assessment of Surgical Clip Marker/Wire Localization in Advanced Breast Cancer - Alamdaran, Seyed Ali; Gharib, Masomeh; Homaee Shandiz, Fatemeh; Bizhani, Oldoz; Forghani Torghaban, Mohammad Naser; Farrokh Tehrani, Donia; Keshtgar, Mohammed (Reports of Radiotherapy and Oncology, 2018)
Objectives: Neoadjuvant chemotherapy in locally advanced breast cancer is associated with a volume decrease of the tumor and needs tumor bed localization. We evaluated the accuracy of the radio-opaque surgical clip marker/wire localization in 35 patients. Methods: Patients who were candidates for breast-conserving surgery after neoadjuvant chemotherapy were enrolled at Omid Hospital, Mashhad University of Medical Sciences, Iran in 2015 - 2017. The lesion localization was performed before the start of chemotherapy. A radio-opaque manually straightened surgical clip was inserted into the mass center by a coaxial needle. After the completion of the neoadjuvant chemotherapy, a localization wire was introduced adjacent to the clip and the surgeon removed the tumor bed. The resected mass was assessed for marginal involvement and location of the clip by the pathologist. Data analysis was performed by SPSS and P values of less than 0.05 were considered significant. Results: The mean maximum diameter of the mass before neoadjuvant chemotherapy was 3.8 ± 1.1 cm. The marker was seen at the center of the lesion in 32 (91.4%) patients and at the para-central part in three patients. All patients had a response to chemotherapy as a decrease in size in 22 patients (63%), and complete effacement of the mass in 13 patients (37%). After chemotherapy, the marker was localized in the peripheral part of the residual mass in six patients. Intra-tumoral clip displacement was detected in 3 patients (8.6%). The clip migration out of the lesion was not seen in any patient. In all of the patients, the tumor bed was resected in the pathology examination and marginal involvement was not seen in any of the cases. Conclusions: In the absence of seed localization, the combination of a surgical clip and wire localization is an easy, safe, available, and accurate choice for localizing the tumor bed in advanced breast cancer patients that are candidates for neoadjuvant chemotherapy.